Investigation of Properties of Zinc Plant Residue Mechanically Activated in Two Types of Mills - Turan, M. D.; Balaz, P. (Pleiades Publishing Ltd, 2020)
Extended milling/mechanical activation properties of zinc plant residue was investigated using two different milling systems, namely, high speed vibrating ball mill and ring mill, comparatively. The zinc plant residue was mixture of gypsum, anglesite, massicot, quartz, maghemite, and franklinite. Zinc plant residue was milled for 1-30 min in high speed vibrating ball mill and ring mill. The obtained samples were characterized using XRD, SEM, particle size distribution, and N-2-BET methods. According to results, it was found that the ring mill caused a further decrease in particle size. Particle size distribution and N-2-BET analyses showed that agglomeration of particles began after 15 min and 5 min milling time for HSBVM and ring mill, respectively.
Keywords: Mechanical activation; zinc; ring mill; high speed vibrating ball mill